(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the main directions of development of customer-oriented policy at small businesses in the field of catering, presents the results of a survey of customers of small businesses in the field of catering from the point of view of their satisfaction with the quality of services offered, analyzes the tools used at small businesses in the field of catering to form a customer-oriented policy.